2015
DOI: 10.1590/s0034-759020150408
|View full text |Cite
|
Sign up to set email alerts
|

The International Growth of a Social Business: A Case Study

Abstract: In developing countries, initiatives have often been undertaken in order to fight social and environmental problems. Since the 1990s, an increase can be seen in corporate social responsibility actions, as well as increasingly strong activities by civil society organizations. Tweenty years ago, companies and civil society organizations stood wide apart from each other, with often conflicting agendas and resistance to mutual collaboration. This reality has changed significantly. Besides the phenomenon of cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
9
0
5
Order By: Relevance
“…Kanie, Haas, Andresen et al (2013) point out that development in an unsustainable way has created a very serious situation, and problems have already reached or are reaching a point of irreversible change, with negative consequences for a healthy planet. However, with greater social commitment on the part of organizations and society, it would be possible to have a positive impact on both social and environmental awareness (KONDO, 2009;MOURA, COMINI and TEODÓSIO, 2015).…”
Section: Recognition Of Social Responsibility Practicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Kanie, Haas, Andresen et al (2013) point out that development in an unsustainable way has created a very serious situation, and problems have already reached or are reaching a point of irreversible change, with negative consequences for a healthy planet. However, with greater social commitment on the part of organizations and society, it would be possible to have a positive impact on both social and environmental awareness (KONDO, 2009;MOURA, COMINI and TEODÓSIO, 2015).…”
Section: Recognition Of Social Responsibility Practicesmentioning
confidence: 99%
“…Among these emerging economies, it is observed that Brazil has sought to promote greater awareness among the population in general (MOURA, COMINI and TEODÓSIO, 2015).…”
Section: Recognition Of Social Responsibility Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 1990s, a growth in corporate social responsibility actions was observed, as well as the intensification of performance in civil society organizations (Moura, Comini & Teodósio, 2015). With this trend, the desire for a career in social businesses has grown among many Generation Y young administrators (Rosolen, 2014).…”
Section: Career Managementmentioning
confidence: 99%